Secondary exophytic glioblastoma of the cerebellopontine angle: a case report and review of the literature - Dai, Lirui; Zhan, Wenyi; He, Shuanghong; Jiang, Shu; Zhou, Peizhi (Frontiers in Oncology, 2026)
PurposeGlioblastoma (GB), a World Health Organization (WHO) grade IV astrocytoma, is the most aggressive primary brain tumor in adults, with a median survival of 12–15 months despite multimodal therapy involving maximal safe resection, radiotherapy, and temozolomide. While GB predominantly arises in the supratentorial region, brainstem glioblastoma (BS-GB) represents an exceptionally rare and clinically devastating subset, accounting for only 1-2% of all GBs.Methods and resultsWe report a case of a 54-year-old male patient who presented with dizziness and diplopia for half a year. Examination revealed abnormal signals in the right cerebellopontine angle, cerebellar hemisphere, and brainstem. After hormone shock and antiviral treatment, the patient’s symptoms did not improve and continued to worsen. We performed a lesion biopsy on the patient. During the operation, we found a space-occupying lesion in the pontocerebellar region. The pathological examination suggested GB. After the surgery, the patient’s symptoms improved and he received regular radiotherapy and chemotherapy.ConclusionCases in which abnormal signals are simultaneously present in the right cerebellopontine angle, cerebellar hemisphere, and brainstem are extremely rare. After craniotomy and exploration, it was found that some of the abnormal signals were GB and some were inflammation. After surgical treatment, the patient’s symptoms were relieved. This case provides treatment ideas for patients suspected of having intracranial inflammatory lesions but who have not shown improvement despite continuous medical treatment, thereby broadening the treatment perspective.